Long-Term Fertilizer-Based Management Alters Soil N2O Emissions and Silicon Availability in Moso Bamboo Forests - Jie Yang; Kecheng Wang; Jiamei Chen; Lili Fan; Peikun Jiang; Rong Zheng (Agronomy)
Long-term intensive management practices in Moso bamboo (Phyllostachys edulis) forests, primarily characterized by repeated fertilizer application, tillage, and biomass harvesting, can alter soil nutrient cycling and ecosystem stability. This study aimed to assess how such fertilizer-based management affects soil N2O emission potential and silicon (Si) availability. We collected soil samples (0–20 cm) from bamboo stands subjected to 0–39 years of intensive management and from adjacent natural broad-leaved forests as a reference. The Soil pH, nitrogen forms, nitrification and denitrification potential, and Si concentrations were measured. The results showed significant nitrogen accumulation and progressive soil acidification with increasing management duration. The nitrification and denitrification potentials were 5.7 and 6.0 times higher in the 39-year-old stand compared to unmanaged bamboo. Meanwhile, the available Si decreased by 20.1%, despite stable total Si levels. The available Si showed strong positive correlations with nitrogen forms and transformation rates. These findings highlight the long-term impact of fertilizer-driven bamboo management on soil biogeochemistry and emphasize the need to consider Si dynamics in sustainable nutrient strategies.